ALTERNATIVE ASSESSMENT METHODS FOR STUDENT GROWTH - Rustamova, Sevinch (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
This paper discusses the importance of alternative assessment in language learning. Unlike traditional tests, it focuses on real communication, reflection, and ongoing progress. By using portfolios, journals, and other authentic tools, teachers can understand learners’ strengths and needs more deeply.